2005
DOI: 10.1016/j.febslet.2005.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐activating factor induces matrix metalloproteinase‐9 expression through Ca2+‐ or PI3K‐dependent signaling pathway in a human vascular endothelial cell line

Abstract: Platelet-activating factor (PAF) augments angiogenesis by promoting the synthesis of a variety of angiogenic factors, via the nuclear factor (NF)-jB activation. Recently, we reported that PAF upregulates MMP-9 expression in a NF-jB-dependent manner. In this study, we investigated the signaling pathway involved in PAF-induced MMP-9 expression in ECV304 cells. Our current data indicate that the Ca 2+ -or phosphatidylinositol 3-kinase (PI3K)-dependent signaling pathway is necessary for PAF-induced MMP-9 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 45 publications
4
24
0
1
Order By: Relevance
“…In fact, previous studies have shown the expression of MMP-9 is under the control of a 2.2-kb upstream regulatory region harboring binding sites for AP-1, Ets2, NF-B, and Sp1, some of which are activated during KSHV infection (19,47,48). In endothelial cells, the expression of MMP-9 is regulated by multiple signaling pathways, such as the phosphatidylinositol 3-kinase pathway (25,39). Further studies are required to define the mechanism by which KSHV regulates the expression and secretion of MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous studies have shown the expression of MMP-9 is under the control of a 2.2-kb upstream regulatory region harboring binding sites for AP-1, Ets2, NF-B, and Sp1, some of which are activated during KSHV infection (19,47,48). In endothelial cells, the expression of MMP-9 is regulated by multiple signaling pathways, such as the phosphatidylinositol 3-kinase pathway (25,39). Further studies are required to define the mechanism by which KSHV regulates the expression and secretion of MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 is present in low quantities in the healthy adult lung but much more abundant in COPD, and the inappropriate expression of MMP9 is thought to contribute to the pathogenesis of COPD . MMP9 expression, whether stimulated by PAF or fibronectin, probably through an action on NF-B, is also regulated by PI3K signaling pathways (Ko et al, 2005). Furthermore, several lines of evidence point to the importance of PI3K in the activation of macrophage and neutrophils, which are key players in COPD inflammation (Thomas et al, 2005).…”
Section: Pi3k In Airway Inflammationmentioning
confidence: 99%
“…It is known that the ERK1/ 2 pathway is necessary for MMP-9 induction by homocysteine, (37) α3β1 integrin (38) and ras oncogene, (39) and that MMP-9 induction by platelet-activating factor iss dependent on PI3K. (40) Integrin signals are thought to stimulate focal adhesion kinase, a tyrosine kinase that leads to activation of PI3K, (41,42) and the PI3K/Akt pathway modulates mitochondrial functions. (43) The results shown in Fig.…”
Section: Discussionmentioning
confidence: 99%